Commentary: Evidential Validity Versus Predictive Validity—The Need for Both. (February 2017) - Montgomery, Alyssa; Dumont, Ron; Willis, John O.
The articles presented in this Special Issue provide evidence for many statistically significant relationships among error scores obtained from the Kaufman Test of Educational Achievement, Third Edition (KTEA)-3 between various groups of students with and without disabilities. The data reinforce the importance of examiners looking beyond the standard scores when analyzing results. Although the data in these articles are powerful by themselves, this commentary explores the potential advantages of considering additional information to increase the practicality of these results. Although statistical significance may provide evidential validity of the results, and the articles inform clinical practice and offer valuable leads for further research that should be pursued, the present authors question whether the data as presented provide sufficient information to determine the predictive and practical utility of these initial results. The next step, we believe, is to extend these novel approaches to data from larger, carefully defined samples of students with specific learning challenges and disabilities.